Transformer T-joint optimization using particle swarm optimization and hemisphere-shape design of the core - Yehya, Omar Sharaf Al-Deen (2017)
Transformers are considered as a key in the transmission and distribution of electrical energy. The increases for electricity have encouraged the manufacturers to produce huge numbers of transformers for different sizes and ratings to work on the electric grid in order to meet market demands. The electrical power engineering and transformer experts seek to achieve the best economic and practical operation of electrical power system transformers, which include minimizing losses that are generated inside the transformers. The losses in transformers can be significantly reduced, especially in the core by improving the performance of the joint design. Several factors and parameters contribute to core losses such as shape of joint, gaps in between the joint parts, thickness of laminations, overlapping, orientation and number of laminations per stack.